Implementasi Penegakan Hukum terhaadap Pencurian Kendaraan Bermotor Studi di Kuningan - Agustin, Agung Gumelar; Hidyat, Sarip; Andriyani, Yani; Akmaddhian, Suwari (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2024)
The National Police of the Republic of Indonesia has the function and task of maintaining public security and order as stated in Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia, the presence of law enforcement members of the police in the midst of society is very much needed to maintain security and order in public. On the other hand, cases of motor vehicle theft have become widespread in society after Covid-19 broke out in Indonesia, resulting in economic disparities and in the midst of the post-Covid economic recovery, many criminal acts of motor vehicle theft have occurred. Problem Formulation: how to regulate law enforcement against motor vehicle theft according to applicable laws and regulations and how the Police implement law enforcement against motor vehicle theft in the Kuningan Police area sector. The research stage involves literature study and field research, data collection techniques using primary, secondary data and using primary legal data, secondary legal data and tertiary legal data, as well as data collection tools using observation and interviews. The research results show that motor vehicle theft is regulated in Law Number 1 of 1946 concerning Criminal Law regulations. The Kuningan Regency Resort Police apparatus has made preventative and repressive efforts as much as possible but is experiencing obstacles due to community factors and community legal culture factors which still do not care about the applicable laws, so that motor vehicle theft still occurs and the intensity is increasing. from 2021 to 2023. Suggestions for the Kuningan Regency Police Department to increase legal awareness efforts and provide guidance to the community regarding efforts to prevent criminal cases of motor vehicle theft.